ALARA and BAT concept of the design of radioactive waste dis - SUGIYAMA, Daisuke; NAKABAYASHI, Ryo; KURODA, Kazuma (Journal of Nuclear Fuel Cycle and Environment, 2024)
This paper reports the results of a survey of regulatory documents to clarify the concepts of ALARA and BAT in UK radioactive waste management and disposal. The results of this survey indicated that ALARA concept has been included in the BAT decision-making process as an indicator to evaluate the reduction of exposure doses. It also indicated that when applying the BAT concept to the selection of options for facility components, it is important to aim for a systematic and balanced selection of options with a view to the facility as a whole, rather than selecting options that can minimize emissions to the environment and exposure doses. It was also shown that long-term uncertainty can be an important indicator when applying the BAT concept to the selection of facility design options for a radioactive waste disposal.